Conference Scene: Pharmacogenomics: from cell to clinic (Part 2). (April 2014) - Siest, Gérard; Medeiros, Rui; Melichar, Bohuslav; Stathopoulou, Maria; Van Schaik, Ron HN; Cacabelos, Ramon; Abt, Peter Meier; Monteiro, Carolino; Gurwitz, David; Queiroz, Jao; Mota-Filipe, Helder; Ndiaye, Ndeye Coumba; et al.
Second International ESPT Meeting Lisbon, Portugal, 26–28 September 2013 The second European Society of Pharmacogenomics and Theranostics (ESPT) conference was organized in Lisbon, Portugal, and attracted 250 participants from 37 different countries. The participants could listen to 50 oral presentations, participate in five lunch symposia and were able to view 83 posters and an exhibition. Part 1 of this Conference Scene was presented in the previous issue of Pharmacogenomics . This second part will focus on: clinical implementation of pharmacogenomics tests; transporters and pharmacogenomics; stem cells and other new tools for pharmacogenomics and drug discovery; from system pharmacogenomics to personalized medicine; and, finally, we will discuss the Posters and Awards that were presented at the conference.